Reappraising Charles Webb's The Graduate (1963): Exploring cultural and historical elements of a character in the contemporary economy. (January 2020) - Watt, Peter; Costea, Bogdan
This article seeks to examine, in a cultural–historical perspective, how the 'graduate' has developed as a character central to a significant segment of the contemporary labour market. The argument begins by showing how the rise of the 'new' or 'knowledge economy' (throughout the 1990s and 2000s) became a new source of pressure on generations entering the world of work. Higher education has been, and continues to be, presented by political, corporate and educational institutions as a core platform upon which future possibilities of personal achievement and accomplishment depend. Gradually, the vocabulary and character of the 'graduate' has become more visible through complex and refined modes of cultural dissemination. The themes through which this character is articulated today have, we argue, cultural roots that are not entirely new. With reference to David Riesman's early understanding of the formation of this kind of cultural 'character', we examine Charles Webb's 1963 novel The Graduate. As a cultural–historical resource, it can be revisited half a century later in order to investigate the historical movement of certain themes and questions that now outline what a 'graduate' could and should be. The imperatives that underlie the labour market for graduate schemes open up questions that pertain not only to immediate matters of employment. Rather, the discourses of 'graduate work' and 'employability' now appropriate deeper concerns regarding the meaning of individual freedom, choice and self-determination. Who is the 'graduate' and what are some of its cultural roots?